REFLECTIONS ON MOTHER TONGUE CONDITIONS IN INDONESIA THROUGH MEDIA TEXT ANALYSIS - Vilya Lakstian Catra Mulia (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2018)
English Text analysis becomes one of many approaches to analyze the dynamics of mother tongue issues whose condition is relatively appalling. Mother tongue (language) is the earliest language acquired by a member of society starting from the cradle of family. Because of its proximity, mother language is close to local language. However, its popularity is less than Bahasa Indonesia and foreign languages. It is reflected on the related texts in media for International Mother Language Day (IMLD). This is descriptive qualitative type of research using criteria-based sampling along with content analysis technique to the related texts of IMLD in the daily printed national newspaper, Kompas. The researcher used Systemic Functional Linguistics to obtain interpersonal: transactional meanings through mood structure analysis from narration, reports, and quotations. Based on the analysis, the study investigated the attitudes presented by participants in the texts to their readers from analysis results of modalization and modulation. This research concluded that the texts were more dominated by language meanings with transaction on information rather than action. This affected on the modes of delivering messages informatively and the orientation of enriching the insights. Indonesia Analisis teks menjadi salah satu pendekatan untuk menemukan dinamika bahasa ibu yang kini dalam kondisi memprihatinkan. Bahasa ibu merupakan bahasa yang paling dekat dan awal diterima masyarakat mulai dari lingkup keluarga. Karena kedekatan itu, bahasa ibu erat kaitannya dengan bahasa daerah. Namun, kepopulerannya kalah dengan bahasa Indonesia dan bahasa asing. Kondisi ini tampak pada teks-teks di media terkait peringatan Hari Bahasa Ibu Internasional (HBII). Penelitian ini bersifat deskriptif kualitatif dengan tehnik cuplikan berkriteria serta dikaji dengan tehnik analisis isi terhadap teks-teks terkait HBII pada koran harian cetak nasional, Kompas. Peneliti menggunakan pendekatan Linguistik Sistemik Fungsional untuk memperoleh makna interpersonal: transaksional melalui analisis struktur mood pada narasi, pelaporan, dan kutipan. Dari analisis tersebut, dieksplorasi juga sikap yang dihadirkan pelibat teks kepada pembacanya dari hasil analisis modalisasi dan modulasi. Penelitian ini menemukan kesimpulan bahwa teks-teks tersebut didominasi oleh makna bahasa dengan transaksi informasi daripada tindakan. Hal ini berdampak pada penyajiannya yang secara informatif dan berorientasi pada menambah wawasan.